2022
DOI: 10.1038/s42003-022-03336-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and salt depletion synergistically boosts glucose metabolism in individual Escherichia coli cells

Abstract: The interaction between a cell and its environment shapes fundamental intracellular processes such as cellular metabolism. In most cases growth rate is treated as a proximal metric for understanding the cellular metabolic status. However, changes in growth rate might not reflect metabolic variations in individuals responding to environmental fluctuations. Here we use single-cell microfluidics-microscopy combined with transcriptomics, proteomics and mathematical modelling to quantify the accumulation of glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 89 publications
5
15
0
Order By: Relevance
“…Our single-vesicle measurements revealed heterogeneity in the permeability of each synthetic lipid type to each metabolite, with some vesicles of each lipid type displaying a decrease in intracellular fluorescence during the delivery of each metabolite while other vesicles displayed an increase in intracellular fluorescence (temporal dependence of single-vesicle fluorescence for archaeal 4ME diether G1PC lipids and bacterial diester G3PE-PG-CA lipids are reported with dashed magenta lines and dashed-dotted blue lines in Figure S1). For example, the coefficient of variations in the permeability of archaeal 4ME diether G1PC vesicles and of bacterial diester G3PE-PG-CA vesicles to aspartic acid, glyceraldehyde and adenine, were 118% and 103%, 60% and 198%, 76% and 108% (Figure S1D, S1G and S1Q, respectively), in accordance with the proposition that lipid membranes are a system with heterogeneous functions [37,[39][40][41][42][43].…”
Section: Microfluidic Screening To Explore Membrane Permeability Char...supporting
confidence: 81%
“…Our single-vesicle measurements revealed heterogeneity in the permeability of each synthetic lipid type to each metabolite, with some vesicles of each lipid type displaying a decrease in intracellular fluorescence during the delivery of each metabolite while other vesicles displayed an increase in intracellular fluorescence (temporal dependence of single-vesicle fluorescence for archaeal 4ME diether G1PC lipids and bacterial diester G3PE-PG-CA lipids are reported with dashed magenta lines and dashed-dotted blue lines in Figure S1). For example, the coefficient of variations in the permeability of archaeal 4ME diether G1PC vesicles and of bacterial diester G3PE-PG-CA vesicles to aspartic acid, glyceraldehyde and adenine, were 118% and 103%, 60% and 198%, 76% and 108% (Figure S1D, S1G and S1Q, respectively), in accordance with the proposition that lipid membranes are a system with heterogeneous functions [37,[39][40][41][42][43].…”
Section: Microfluidic Screening To Explore Membrane Permeability Char...supporting
confidence: 81%
“…It is worth noting that these findings were not dictated by oxygen limitation or low metabolic activity as in the case of biofilms ( Walters III et al, 2003 ). In fact, we ( Łapińska et al, 2019 ; Glover et al, 2022 ) and others ( Wang et al, 2010 ) have previously demonstrated that nutrients, including oxygen and metabolites, uniformly distribute across the whole length of bacteria hosting channels in our microfluidic device.…”
Section: Resultsmentioning
confidence: 69%
“…Using minimum inhibitory concentration (MIC) assays we found that the fluorescent derivatives of polymyxin B, octapeptin, tachyplesin, vancomycin, and linezolid maintained the antibiotic activity of the parent drug against E. coli , whereas the fluorescent derivatives of roxithromycin, trimethoprim, and ciprofloxacin displayed a 3-fold, 64-fold, and 256-fold increase compared to the parent drug, respectively ( Appendix 1—table 1 ). Next we used each probe in our microfluidics-microscopy platform ( Łapińska et al, 2019 ; Cama et al, 2020 ; Stone et al, 2020 ; Glover et al, 2022 ) to quantify the dynamics of the accumulation of each antibiotic in individual bacteria in real-time ( Figure 1B and Figure 1—source data 1 ). Briefly, we loaded an aliquot of a stationary phase clonal bacterial culture in a microfluidic device equipped with small parallel channels, each hosting between one and six bacteria ( Łapińska et al, 2019 ; Cama et al, 2020 ; Stone et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We adapted our recent single-cell platform ( 18 , 31 , 39 , 45 , 46 ) to investigate the response of hundreds of individual stationary-phase E. coli cells to ampicillin, ciprofloxacin, and protein Ψ-capsids at their MIC (5, 0.125, and 15 μg/mL, respectively). We found notable differences in response to these three agents within a clonal E. coli population: individual E. coli cells elongated during a 3-h treatment with ampicillin and ciprofloxacin ( Fig.…”
Section: Resultsmentioning
confidence: 99%